Komunikasi Keluarga Sabeulah Dalam Konteks Kesundaan (Studi Etnografi Komunikasi Tentang Komunikasi Ibu Atau Ayah Dengan Anak Di Kabupaten Ciamis) - Zikri Fachrul Nurhadi (Jurnal Komunikasi, 2014)
Abstract: This research is motivated by family tendency "sabeulah" or a divorce in Kabupaten Ciamis from year to year that has increased . This increase, giving parenting patterns into two positions that children live with a mother or a father ?sabeulah?, and divorce statistics in the office of religious Ciamis district is also increasing. Based on the data obtained from the year 2009 as many as 3.751, while in 2013 to 2013 increased to 5.319. With the ethnography of communication approach, this study may reveal patterns of communication in the family ?sabeulah? happened to mom or dad ?sabeulah?. The subjects in this study is a mother or father whose status is Randa and duda who lives with the child due to the economic problems of divorce, death, and infidelity. While the data collection techniques that is used in this study is participant observation, in-depth interviews, and study documentation. The results of this study indicate that in single parents family communication mother or father who gets priority for a child to be socialized are religious values, harmony, obedience, responsibility, discipline, respect (courtesy), achievement and honesty. Single parents family communication components that occur in the mother or father made up genre, topic, purpose, setting, participants, shape of message, the message content, sequence of actions, rules of interaction, and norms. While single parents family communication patterns that occur in the mother or the father consists of: patterns of communication about compliance, patterns of communication about expectations, patterns of communication about money management, communication patterns on the role of relatives, about the future of communication patterns, and patterns of communication on learning and experience. Single parents family communication that occurs in the mother or the father produces several perspectives such as: single parents family communication models through interpersonal communication, single parents family communication models through verbal and non-verbal symbols, models are colectivistic single parents family communication, single parents family communication models of the type seen in the face problems, single parents family communication models role in interpersonal communication perspective, the values that formed in single parents family culture, single parents family communication models about the role of extended family or relatives, single parents family communication models viewed from the perspective of symbolic interaction and communication models single parents family in perspective silih asah, asih and asuh).Abstrak:Penelitian ini dilatarbelakangi adanya kecenderungan keluarga ??sabeulah?? atau tingkat perceraian di Kabupaten Ciamis dari tahun ke tahun mengalami peningkatan. Peningkatan ini, memberikan pola pengasuhan anak berada pada dua posisi yaitu anak yang hidup bersama seorang ibu maupun dengan seorang ayah sabeulah, serta angka statistik perceraian yang ada di Kantor Pengadilan Agama Kabupaten Ciamis pun meningkat. Berdasarkan data yang diperoleh mulai dari tahun 2009 sebanyak 3.751 sampai dengan tahun 2013 meningkat menjadi 5.319. Dengan pendekatan etnografi komunikasi, penelitian ini dapat mengungkap pola komunikasi pada keluarga sabeulah yang terjadi pada ibu atau ayah sabeulah. Adapun subjek pada penelitian ini adalah ibu atau ayah yang berstatus randa dan duda yang tinggal bersama anak akibat perceraian masalah ekonomi, kematian, perbedaan pandangan dan perselingkuhan. Sedangkan teknik pengumpulan data yang digunakan pada penelitian ini adalah pengamatan partisipan, wawancara mendalam, dan studi dokumentasi. Hasil penelitian ini menunjukkan bahwa dalam komunikasi keluarga sabeulah pada ibu atau ayah yang mendapat prioritas untuk dapat disosialisasikan kepada anak adalah nilai religius, kerukunan, ketaatan, tanggungjawab, disiplin, hormat (sopan santun), pencapaian prestasi dan kejujuran. Komponen komunikasi keluarga sabeulah yang terjadi pada ibu atau ayah terdiri atas genre, topik, tujuan, setting, partisipan, bentuk pesan, isi pesan, urutan tindakan, kaidah interaksi, dan norma-norma. Sedangkan pola komunikasi keluarga sabeulah yang terjadi pada ibu atau ayah terdiri atas: pola komunikasi tentang kepatuhan, pola komunikasi tentang harapan, pola komunikasi tentang pengaturan uang, pola komunikasi tentang peran kerabat, pola komunikasi tentang masa depan, dan pola komunikasi tentang pembelajaran dan pengalaman. Komunikasi keluarga sabeulah yang terjadi pada ibu atau ayah menghasilkan beberapa perspektif antara lain: model komunikasi keluarga sabeulah melalui komunikasi interpersonal, model komunikasi keluarga sabeulah melalui simbol verbal dan non verbal, model komunikasi keluarga sabeulah bersifat kolektivistik, model komunikasi keluarga sabeulah dilihat dari tipe dalam menghadapi masalah, model komunikasi keluarga sabeulah tentang peran dalam perspektif komunikasi interpersonal, nilai-nilai yang terbentuk dalam budaya keluarga sabeulah, model komunikasi keluarga sabeulah tentang peran keluarga besar atau kerabat, model komunikasi keluarga sabeulah dilihat dari perspektif interaksi simbolik serta model komunikasi keluarga sabeulah dalam perspektif silih asah, asih dan asuh.